1995
DOI: 10.1111/j.1600-0722.1995.tb00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereologic study of cyclosporin A‐induced gingival overgrowth in renal transplant patients

Abstract: Gingival biopsies were taken from 13 renal transplant patients (mean age 26.5 yr), 11 of whom exhibited cyclosporin A (CsA)-induced gingival overgrowth. Control material was obtained from seven volunteers (mean age 28 yr). Gingival tissue components were analyzed by quantitative microscopy (stereology) on 5-microns-thick sections of interdental papillae. The volume density (Vv) of different tissue components and the surface density of epithelial ridges were calculated by conventional point and intersection cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The relationship between CsA treatment and gingival overgrowth has been reported in human and some experimental models, 2,6,8,31‐35 although the exact etiology is not understood. The pathophysiological mechanisms of CsA‐induced gingival overgrowth may include features such as an increase in the epithelial thickness and an increase in the proliferation of connective tissue components 4,6,8,9 . The other important feature of gingival overgrowth tissue is increased vascularization, and previous studies have shown that CsA increases the cross‐sectional area of blood vessels in GCT 8,9 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between CsA treatment and gingival overgrowth has been reported in human and some experimental models, 2,6,8,31‐35 although the exact etiology is not understood. The pathophysiological mechanisms of CsA‐induced gingival overgrowth may include features such as an increase in the epithelial thickness and an increase in the proliferation of connective tissue components 4,6,8,9 . The other important feature of gingival overgrowth tissue is increased vascularization, and previous studies have shown that CsA increases the cross‐sectional area of blood vessels in GCT 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…Various side effects associated with CsA therapy have been described, including nephropathy, hepatotoxicity, neurotoxicity, hypertension, and gingival overgrowth 3,4 . Gingival overgrowth is characterized by increased epithelial thickness, enlargement of connective tissue, and increased vascularization 5‐9 . According to previous histomorphometric studies, CsA‐induced gingival overgrowth shows increases in the mean cross‐sectional area of epithelium, connective tissue, and blood vessel profile 4,6,8,9 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The volume density of oral epithelium significantly increased in cyclosporine A-induced gingival overgrowth as compared to non-medicated controls [20]. Epithelial thickening, induced by nifedipine [21] and cyclosporine A, is related to thickening of spinous layer [20].…”
Section: Pathogenesismentioning
confidence: 98%
“…Epithelial thickening, induced by nifedipine [21] and cyclosporine A, is related to thickening of spinous layer [20]. Brown, Beawer, Bottomlay [22] suggested a functional heterogenecity between subgroups of fibroblasts in normal tissues.…”
Section: Pathogenesismentioning
confidence: 98%